An Empirical Study on the Effects of Managerial Competence on Firm Profitability - Beny Mwenda; Magwana Ngollo; Amosi Mwasota (Ilomata International Journal of Tax and Accounting, 2023)
Profits are generated by managing assets and using them wisely to create revenues that exceed costs. This study aimed to analyse the effects of managerial competence on firm profitability listed in the Dar es Salaam stock exchange (DSE). The quantitative research design was used to collect, analyse and interpret data in this research while Panel Regression Model was selected to analyse the influence of Managerial competence on profitability of listed firms. POLS technique was used to check robustness and Diagnostic tests were used to meet the criteria of regression analysis. The regression analysis indicate that managerial competence had a significant effect on firm profitability. Raising managerial competence has the potential to significantly increase business profitability, as managers play a key role in an organization's overall functioning. The researchers suggested that shareholders should thoroughly analyse potential managers' competencies and credentials before allocating managerial duties since hiring a competent management team is likely to have a beneficial impact on the firm's profitability. Shareholders should strive to reduce the risk of choosing managers who lack the requisite abilities to maximize the firm's profitability by performing due diligence in the selection process.